Risk factors for hidradenitis suppurativa: a pilot study - Schmitt,Juliano Vilaverde (2012)
The hidradenitis suppurativa is a chronic debilitating inflammatory disease whose etiology is not fully understood. We conducted a pilot case-control study matched by sex and age with other dermatological patients to analyze possible risk factors associated with this disease. We included 15 cases and 45 controls, 67% were women. Bivariate and multivariate logistic regression analysis identified significant association with smoking, higher body mass index and family history. The use of hormonal contraceptives was less frequent in women with hidradenitis.